Interação no rádio: a participação do ouvinte no programa debates do povo - Andrade, Mônica Araújo (2014)
The radio is just not seen as conveying information, but a media able to establish ways that generate certain direction. We see an inclusion of the listener in the construction of programs, is exposing their life stories, commenting on facts, answering questions, choosing subjects and participating in some form of radio programming. This insertion of the listener in radio programs is generally thought of as a constituent element of the message. This study aims to analyze the participation of the listener and the forms of interaction in the " Debates of the People" that thirty- past two years is the schedule for CBN Fortaleza. The investigation was conducted through observation in studio, interview, transcription, content analysis and association analysis. This is a qualitative and quantitative research while. We found that the listeners of the program had no acceptance of interactive tools such as the Internet and social networks to make their holdings. In clipping analyzed, we noted that the participation of the listener was selected according to their relationship and proximity to the topic discussed. Also detected that the opinion is superior to the listener questions on the topic. The presenter has the function to put the questions in the listener program. Among the public comments are questions and opinions on the subject and speaks of the debaters. Among the authors, use Barbosa (2009 ), Ferraretto (2007 ), Lopez (2010 ), Ortriwano (2001 ), Peruzzo (2004 ), Prata (2009 ), Primo (2006 ), Thompson (2009 ), among others